Vascular smooth muscle cell proliferation as a therapeutic target. Part 2: Natural products inhibiting proliferation - Uhrin, Pavel; Wang, Dongdong; Mocan, Andrei; Waltenberger, Birgit; Breuss, Johannes M.; Tewari, Devesh; Mihaly-Bison, Judit; Huminiecki, Łukasz; Starzyński, Rafał R.; Tzvetkov, Nikolay T.; Horbańczuk, Jarosław; Atanasov, Atanas G. (Biotechnology advances, 2018)
Many natural products have been so far tested regarding their potency to inhibit vascular smooth muscle cell proliferation, a process involved in atherosclerosis, pulmonary hypertension and restenosis. Compounds studied in vitro and in vivo as VSMC proliferation inhibitors include, for example indirubin-3′-monoxime, resveratrol, hyperoside, plumericin, pelargonidin, zerumbone and apamin. Moreover, taxol and rapamycin, the most prominent compounds applied in drug-eluting stents to counteract restenosis, are natural products. Numerous studies show that natural products have proven to yield effective inhibitors of vascular smooth muscle cell proliferation and ongoing research effort might result in the discovery of further clinically relevant compounds.